(Invited) Integration Challenges of Ferroelectric Hafnium Oxide Based Embedded Memory. (9th September 2015) - Müller, Johannes; Polakowski, Patrick; Paul, Jan; Riedel, Stefan; Hoffmann, Raik; Drescher, Maximilian; Slesazeck, Stefan; Müller, Stefan; Mulaosmanovic, Halid; Schröder, Uwe; Mikolajick, Thomas; Flachowsky, Stefan; et al.
Abstract : One of the key challenges in the development of embedded memory solutions is to ensure their compatibility to CMOS processing and to reduce the added complexity to a minimum. Especially the parallel implementation of charge based one-transistor memories in the FEoL, such as e.g. floating gate devices, together with advanced transistor technologies proves rather challenging. In contrast to that, an alternative one-transistor memory concept based on ferroelectric hafnium oxide closely resembles state of the art high-k metal gate devices and therewith promises a greatly simplified integration. Here we investigate the impact of strain, thermal budget and work function engineering, usually applied to high-k metal gate technologies, on material properties as well as on the memory performance of hafnium oxide based ferroelectric field effect transistors. Key challenges related to a modified gate etch and the integration of different hafnium oxide thicknesses will be discussed.